How People Apply Mental Accounting Philosophy to Investment Risk? - Mascareñas, Juan; Yan, Fangyuan (International Journal of Economics and Financial Issues, 2017)
In this article, the authors discuss the theme of mental accounting, which is the combination of psychology and finance. It suggests that the investment portfolio should be determined by the investors risk appetite and profitability preference. Not all investors want to take risks to obtain profits, and not all investors will give up their profits (or for sake their profits) because they are afraid of risks. Investors are different, AS they make decisions according to their own risk and return profiles. Unlike the traditional CAPM theory, we consider that risk and return portfolios have different levels in line with the investors’ mental accounts of risk and profits to meet their investment expectations. Investors will carry out investment activities only when their psychological needs are met. Keywords: Mental Accounting; Investors Risk Appetite; BETA and Return investment portfolio. JEL Classifications: B26; F39; G02